The speech processing lexicon : neurocognitive and behavioural approaches - Kotzor, Sandra; Lahiri, Aditi (Phonology and phonetics, 2017)
In this book, some of today's leading neurolinguists and psycholinguists provide insight into the nature of phonological processing using behavioural measures, computational modeling, EEG and fMRI. The essays cover a range of topics including categorization, acoustic variability and invariance, underspecification, talker-specificity and machine learning, focusing on the acoustics, perception, acquisition and neural representation of speech.